Surface Tension Measurements on Iron and Iron-Oxygen Alloys by the Oscillating Drop Technique - Murarka, Ram N. (My University, 1971)
The oscillating drop technique was used to measure the surface tension of pure liquid iron and its oxygen alloys in the range 0 to 600 ppm oxygen. An attempt has been made to investigate how these measurements can be used for future kinetics studies.
Title: Surface Tension Measurements on Iron and Iron-Oxygen Alloys by the Oscillating Drop Technique, Author: Ram N. Murarka, Location: Thode